Improving quality and shelf-life of whole chilled Pacific white shrimp (Litopenaeus vannamei) by ozone technology combined with modified atmosphere packaging. (January 2019) - Gonçalves, Alex Augusto; Lira Santos, Tanyla Cybelly
Abstract: The objective of the present study was to evaluate the combined use of ozone technology with modified atmosphere packaging as an alternative to ensure the microbiological safety, physicochemical quality and increment of the shelf life of whole Pacific white shrimp ( Litopenaeus vannamei ). Shrimp samples were pretreated by immersion in cold ozonated water (1 ppm, 10 min, 15 °C) and chlorinated water (5 ppm, 10 min, 15 °C). Control group samples were immersed on cold (15 °C) distilled water for 10 min. After immersion, shrimp samples were drained, packed either in atmospheric air (Control), or in modified atmosphere (100% CO2 ), and stored under refrigeration (4 ± 0.5 °C) for 12 days. Every third day samples were withdrawn for the microbiological, physicochemical and sensorial analyzes. Ozonated water followed by MAP increased shelf life (up to 24 days) when compared to chlorinated water (up to 11 days) and control group (up to 9 days), maintained the acceptable sensorial attributes and the low melanosis index, ensured low microbial counts, and finally preserved the physicochemical parameters. Thus, the ozonated water treatment associated with modified atmosphere packaging could be an alternative to expand the seafood shelf life while maintaining its safety and quality. Highlights: Ozone as a pre-treatment to MAP increases shelf life more than twice. Combined effects (Ozone and MAP) can be an alternative to extending the seafood shelf life. Ozone and MAP maintain the seafood safety and quality up to 24 h of storage under refrigeration.